Distinguishing Individual Linkages of Personal Records from Family Linkages - Newcombe, H. B. (Methods of Information in Medicine, 1993)
Errors occur in the automated linkage of medical and other records into personal histories, when household and family identifiers get wrongly treated in the same way as the strictly personal identifiers. This is because overwhelming evidence that two records refer to the same household or family, does not mean they necessarily represent the same person. Current practice in probabilistic record linkage fails to make this distinction, and combines indiscriminately the calculated odds from the mix of identifiers pertaining to all three sorts of entity. A tactic is described that avoids the resulting problem of mistaken personal identity. It does so by first converting composite odds from comparisons of household and family particulars, to a magnitude that contributes correctly to the overall evidence in favour of a strictly personal linkage.
Keywords: Record Linkage; Probabilistic Linkage; Patient Histories; Personal Record Updating; File Maintenance